2010
DOI: 10.1371/journal.pone.0013063
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Molecular Characterization of H9N2 Influenza Isolates from Chickens in Northern China from 2007–2009

Abstract: The repeated transmission to pigs and humans, and the long-term endemicity in terrestrial poultry of H9N2 viruses in China lend urgency to the study of their ecology and pathogenicity. In the present paper, we reported an H9N2 virus sublineage isolated from chickens in northern China from 2007 to 2009 has high lethality for mice. Phylogenetic analysis of the full genome indicated that six representative H9N2 isolates shared high homology to each other, and they clustered in the same sublineage with other H9N2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 48 publications
(122 reference statements)
1
54
0
Order By: Relevance
“…By comparison of their shedding time (Fig. 4C), G57 viruses had longer shedding time until 7 dpi in contact vaccinated chickens with high antibody titers (10)(11)(12). Although the shedding time of ZB/07 was similar with those of G57 viruses, the numbers of H9N2-positive chickens was less (Fig.…”
Section: Significancementioning
confidence: 87%
See 3 more Smart Citations
“…By comparison of their shedding time (Fig. 4C), G57 viruses had longer shedding time until 7 dpi in contact vaccinated chickens with high antibody titers (10)(11)(12). Although the shedding time of ZB/07 was similar with those of G57 viruses, the numbers of H9N2-positive chickens was less (Fig.…”
Section: Significancementioning
confidence: 87%
“…The vaccinated chickens were divided into groups with low antibody levels (HI titer,(6)(7)(8)(9) and high antibody levels (HI titer,(10)(11)(12). Nine viruses used in the above unvaccinated chicken experiment (Fig.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Since the first isolation from terrestrial birds (quails) in 1988, H9N2 became prevalent in China and, occasionally, infected a wide range of species, including humans, dogs, cats, pigs, and a wide variety of domesticated birds (Peiris et al, 1999;Xu et al, 2004;Bi et al, 2010;Zhang et al, 2013). It has been reported that H9N2 might provide internal genes to the lethal 1997 Hong Kong H5N1 viruses that caused six fatal cases out of 18 infected patients (Guan et al, 1999).…”
Section: Introductionmentioning
confidence: 99%